IMPACT OF GENDER ON THE EFFECTIVENESS OF COGNITIVE RESTRUCTURING TECHNIQUE IN THE REDUCTION OF TEST ANXIETY AMONG SENIOR SECONDARY SCHOOL STUDENTS IN BENIN METROPOLIS, EDO STATE (Journal of Guidance and Counselling Studies, 2022)
This study examined the Impact of Gender on the Effectiveness of Cognitive Restructuring Technique in the reduction of test anxiety among secondary school students in Benin metropolis of Edo state. Two Hypotheses were formulated and tested at 0.05 level of significant. The pre-test post-test, control group quasi experimental design was used for the study. The students were assigned to one treatment group and a placebo control group. The instrument used for collection of data was the Test Anxiety Inventory (TAI). The study revealed that Cognitive Restructuring Technique is effective in the reduction of test anxiety scores among secondary school students in Benin metropolis of Edo state. The study further revealed a significant impact of gender on the effectiveness of Cognitive restructuring technique. Cognitive restructuring technique was more effective for females than males on the reduction of test anxiety scores. It was recommended that the school counsellors can use Cognitive restructuring technique to manage test anxiety among students. Cognitive Restructuring techniques should preferably be used for female students since the technique is more effective for females in reducing test anxiety scores than males.
Keywords: Cognitive Restructuring technique; Gender; Test; Anxiety; Students